2022
DOI: 10.1039/d2em00032f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating atmospheric mercury (Hg) uptake by vegetation in a chemistry-transport model

Abstract: Mercury (Hg), a neurotoxic heavy metal, is transferred to marine and terrestrial ecosystems through atmospheric transport. Recent studies have highlighted the role of vegetation uptake as a sink for atmospheric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 94 publications
2
31
0
Order By: Relevance
“…The year-round litterfall flux of evergreen forests may explain the absence of seasonal variation of Hg 0 concentration in the SH. A recent study has also shown that model estimates of Hg 0 uptake based on data from temperate NH forests underestimated observed fluxes measured in the Amazon (Feinberg et al 2022 ). Integrating model processes that increase Hg 0 uptake in tropical forests, such as higher LAI, resulted in better agreement between observed and modelled Hg 0 dry deposition velocity and atmospheric Hg 0 concentrations and seasonal variations, both in the tropical and in the midlatitude locations (Feinberg et al 2022 ).…”
Section: Mercury Deposition Via Litterfall and Throughfallmentioning
confidence: 97%
See 1 more Smart Citation
“…The year-round litterfall flux of evergreen forests may explain the absence of seasonal variation of Hg 0 concentration in the SH. A recent study has also shown that model estimates of Hg 0 uptake based on data from temperate NH forests underestimated observed fluxes measured in the Amazon (Feinberg et al 2022 ). Integrating model processes that increase Hg 0 uptake in tropical forests, such as higher LAI, resulted in better agreement between observed and modelled Hg 0 dry deposition velocity and atmospheric Hg 0 concentrations and seasonal variations, both in the tropical and in the midlatitude locations (Feinberg et al 2022 ).…”
Section: Mercury Deposition Via Litterfall and Throughfallmentioning
confidence: 97%
“…The Hg uptake capacity in evergreen tropical forests is likely favoured by two factors: the large leaf area index (LAI) and the longer leaf lifespan (the time at which the leaves from a cohort emerged until they dropped) (Wohlgemuth et al 2020 ; Feinberg et al 2022 ). Plants with higher LAI and longer leaf lifespan have a much larger capacity to uptake Hg 0 .…”
Section: Mercury Deposition Via Litterfall and Throughfallmentioning
confidence: 99%
“…These methods now confirm, across all biomes, that direct foliar and soil Hg 0 uptake ‘deposits’ far more atmospheric Hg to soils (75%), and to lakes and coasts, than Hg II wet and dry deposition alone (25%) (Zheng et al 2016 ; Obrist et al 2018 ). Important global Hg 0 deposition to land and oceans implies different climate change sensitivity where factors such as (de-)forestation need to be considered (Feinberg et al 2022 ). b Hg release to air, land and water.…”
Section: Global Biogeochemical Mercury Cyclingmentioning
confidence: 99%
“…The reduction in the vegetation sink is expected to be particularly large in the southern Amazon, where conversion of forests to agriculture is occurring at one of the highest rates in the world (Salazar et al 2007 ; FAO 2020 ; Feinberg et al 2022 ). Specifically for the Brazilian Amazon, it has been estimated that about 450,000 km 2 of forest have been deforested since 1990, with deforestation rates that increased by a further 47–75% between 2019 and 2021, relative to 2018 values (Instituto Nacional de Pesquisas Espaciais 2022 ).…”
Section: Fire and Deforestationmentioning
confidence: 99%
“…As discussed above, the reduced vegetation sink will likely be accompanied by increased soil Hg emissions, further increasing atmospheric Hg concentrations. As an extreme example of the potential consequences of the continuous tropical deforestation on re-mobilization of Hg stored in the terrestrial ecosystem, a recent model study simulating complete conversion of Amazonian rainforest to savanna found a 63% decrease in Hg deposition to the Amazon region, equivalent to more than 400 Mg Hg y −1 (Feinberg et al 2022 ). In response, the model showed an increased Hg deposition flux to the ocean of 283 Mg Hg y −1 that was most pronounced in the Eastern Pacific, with implications for aquatic ecosystems and human exposure pathways (Feinberg et al 2022 ).…”
Section: Fire and Deforestationmentioning
confidence: 99%